Improving access to Chagas disease diagnosis and etiologic treatment in remote rural communities of the Argentine Chaco through strengthened primary health care and broad social participation. - Paula Sartor; Ivana Colaianni; M Victoria Cardinal; Jacqueline Bua; Héctor Freilij; Ricardo E Gürtler (Public Library of Science (PLoS), 2017)
BACKGROUND:Rural populations in the Gran Chaco region have large prevalence rates of Trypanosoma cruzi infection and very limited access to diagnosis and treatment. We implemented an innovative strategy to bridge these gaps in 13 rural villages of Pampa del Indio held under sustained vector surveillance and control. METHODOLOGY:The non-randomized treatment program included participatory workshops, capacity strengthening of local health personnel, serodiagnosis, qualitative and quantitative PCRs, a 60-day treatment course with benznidazole and follow-up. Parents and healthcare agents were instructed on drug administration and early detection and notification of adverse drug-related reactions (ADR). Healthcare agents monitored medication adherence and ADRs at village level. PRINCIPAL FINDINGS:The seroprevalence of T. cruzi infection was 24.1% among 395 residents up to 18 years of age examined. Serodiagnostic (70%) and treatment coverage (82%) largely exceeded local historical levels. Sixty-six (85%) of 78 eligible patients completed treatment with 97% medication adherence. ADRs occurred in 32% of patients, but most were mild and manageable. Four patients showing severe or moderate ADRs required treatment withdrawal. T. cruzi DNA was detected by qPCR in 47 (76%) patients before treatment, and persistently occurred in only one patient over 20-180 days posttreatment. CONCLUSIONS AND SIGNIFICANCE:Our results demonstrate that diagnosis and treatment of T. cruzi infection in remote, impoverished rural areas can be effectively addressed through strengthened primary healthcare attention and broad social participation with adequate external support. This strategy secured high treatment coverage and adherence; effectively managed ADRs, and provided early evidence of positive therapeutic responses.